Outcomes of laparoscopic revisional conversion of sleeve gastrectomy to Roux-en-Y gastric bypass: Diff erent strategies for obese and non-obese Asian patients - Ming-Hsien Lee; Owaid M. Almalki; Wei-Jei Lee; Tien-Chou Soong; Shu-Chun Chen (Asian Journal of Surgery, 2023)
Summary: Background: Sleeve gastrectomy (SG) is the most performed bariatric procedure now. Some patients would necessitate a revision to Roux-en-Y gastric bypass (RYGB) as a salvage procedure for intractable gastroesophageal reflux disease (GERD). However, outcome of the revision in Asians with co-existed obesity and those non-obese is not clear. Methods: We retrospectively reviewed the data of patients who underwent revisional laparoscopic RYGB after SG between 2007 and 2019 for intractable GERD with data of one year follow-up. Pre-operative clinical data, perioperative outcomes, GERD symptoms, weight loss and medication details were analyzed. Patients were classified into those with body mass index (BMI) ≥ 25 and < 25 kg/m2. Results: Fifty-five patients (44 women, 11 men; mean age 42.5 years) were included. Mean interval from the initial SG to revision surgery was 51.2 months (range, 5–132). Mean body mass index before SG was 34.6 kg/m2, whereas that before revision surgery was 27.6 kg/m2. All the patients required continue proton pump inhibitor (PPI) to control the GERD symptoms before surgery. Among them, 36 (65.4%) patients in the obese group received long BP limb (>100 cm) RYGB for associated obesity but the common channel was assured to ≥ 400 cm or 70% of small bowel length, the other 19 (34.6%) patients in the non-obese group received standard BP limb (<100 cm) RYGB. There was no difference in basic characters between the two groups before revision surgery except a higher mean BMI (30.0 vs. 22.2 kg/m2, p < 0.001), blood pressure and triglyceride in obese group. One year after revision surgery, all the patients had improved GERD symptoms but only 33 (60%) can completely wave PPI, without difference between the 2 groups. Obese group with a long BP limb RYGB had a significant higher % total weight loss (TWL) than non-obese group (%TWL 9.1% vs. −3.1%, p = 0.005). Conclusion: Laparoscopic revision to RYGB is a safe and effective treatment for patients with intractable GERD after SG but some patients may still have residual GERD symptoms. Using a modified RYGB technique in revision surgery may help in weight reduction for obese Asian patients.